2008
DOI: 10.1161/hypertensionaha.107.098459
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-Induced Extracellular Signal-Regulated Kinase 1/2 Activation Is Mediated by Protein Kinase Cδ and Intracellular Calcium in Adult Rat Cardiac Fibroblasts

Abstract: Abstract-Angiotensin II (Ang II)-induced proliferation of cardiac fibroblasts is a major contributing factor to the pathogenesis of cardiac fibrosis. Ang II activates extracellular signal-regulated kinase (ERK) 1/2 to induce cardiac fibroblast proliferation, but the signaling pathways leading to ERK 1/2 activation have not been elucidated in these cells.The goal of the current study was to identify the intracellular mediators of Ang II-induced ERK 1/2 activation in adult rat cardiac fibroblasts. We determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
74
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 38 publications
5
74
1
Order By: Relevance
“…Several authors have suggested a role for PKC in ERK1/2 activation by GPCR (34,35), although another recent report indicates that inhibition of PKC in adult cardiomyocytes has no effect in ERK1/2 activation by G q -coupled GPCR (36). However, this is the first report to show a direct link between G␣ q and PKC and to establish a role for such association in the stimulation of the ERK5 MAPK cascade by GPCR.…”
Section: Discussionmentioning
confidence: 67%
“…Several authors have suggested a role for PKC in ERK1/2 activation by GPCR (34,35), although another recent report indicates that inhibition of PKC in adult cardiomyocytes has no effect in ERK1/2 activation by G q -coupled GPCR (36). However, this is the first report to show a direct link between G␣ q and PKC and to establish a role for such association in the stimulation of the ERK5 MAPK cascade by GPCR.…”
Section: Discussionmentioning
confidence: 67%
“…Consistent with a potential role for this pathway in cardiovascular disease, the same injurious stimuli such as ANG II and smoking, which are well known to trigger fibrosis, can trigger the activation of fibroblasts to a synthetic phenotype resulting in reparative fibrosis (38,56). This process is initiated by TGF-␤, which is typically produced in response to cellular damage and hormones such as ANg II (22,38). TGF-␤, in turn, stimulates the expression of genes that are characteristic of myofibroblasts, including smooth muscle actin, fibronectin, and osteopontin (25).…”
Section: Discussionmentioning
confidence: 78%
“…A heterozygous deletional mutant of ROCK-I (predominantly expressed in the vasculature and heart) is characterized by reduced perivascular fibrosis (43). Consistent with a potential role for this pathway in cardiovascular disease, the same injurious stimuli such as ANG II and smoking, which are well known to trigger fibrosis, can trigger the activation of fibroblasts to a synthetic phenotype resulting in reparative fibrosis (38,56). This process is initiated by TGF-␤, which is typically produced in response to cellular damage and hormones such as ANg II (22,38).…”
Section: Discussionmentioning
confidence: 92%
“…44,82 However, Ang II induced proliferation of cardiac fibroblasts through ERK1/2 cascade. [83][84][85] This prompted us to evaluate the activation of the ERK pathway in renal fibroblasts and its dependence on TRPC3; TRPC3 blockade resulted in ERK1/2 phosphorylation inhibition, which was further validated by selective ERK1/2 inhibition resulting in decreased cell proliferation. TRPC3-mediated activation of ERK1/2 was dependent on Ca…”
Section: Discussionmentioning
confidence: 99%